2012
DOI: 10.4049/jimmunol.1101600
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes, but Not Microglia, Rapidly Sense H2O2 via STAT6 Phosphorylation, Resulting in Cyclooxygenase-2 Expression and Prostaglandin Release

Abstract: Emerging evidence has established that astrocytes, once considered passive supporting cells that maintained extracellular ion levels and served as a component of the blood–brain barrier, play active regulatory roles during neurogenesis and in brain pathology. In the current study, we demonstrated that astrocytes sense H2O2 by rapidly phosphorylating the transcription factor STAT6, a response not observed in microglia. STAT6 phosphorylation was induced by generators of other reactive oxygen species (ROS) and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 63 publications
(67 reference statements)
1
25
0
Order By: Relevance
“…Nevertheless, STAT6 is a key component of the intracellular pathway downstream of IL-4 signaling, and the IL-4-STAT6 axis is likely to orchestrate various phenotypes of alternatively activated astrocytes, including the expression of specific phenotypic markers and neuroprotective molecules. A recent study found that phosphorylation of STAT6 was induced by IL-4 in astrocytes (77), which concurs with our finding that STAT6 was phosphorylated in IL-4-activated astrocytes. In addition, we present evidence that LCN2 targets IL-4-STAT6 signaling to inhibit the alternative activation of astrocytes (see later discussion).…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, STAT6 is a key component of the intracellular pathway downstream of IL-4 signaling, and the IL-4-STAT6 axis is likely to orchestrate various phenotypes of alternatively activated astrocytes, including the expression of specific phenotypic markers and neuroprotective molecules. A recent study found that phosphorylation of STAT6 was induced by IL-4 in astrocytes (77), which concurs with our finding that STAT6 was phosphorylated in IL-4-activated astrocytes. In addition, we present evidence that LCN2 targets IL-4-STAT6 signaling to inhibit the alternative activation of astrocytes (see later discussion).…”
Section: Discussionsupporting
confidence: 82%
“…We have reported that, in brain astrocytes, H 2 O 2 administration results in activation of signaling pathways by inducing protein phosphorylation via lipid rafts [33, 36, 37]. To ascertain whether lipid rafts are involved in H 2 O 2 -induced phosphorylation of STAT-6 in T cells, we pretreated Jurkat cells with methyl-β-cyclodextrin (MβCD), a cholesterol depleting agent that disrupts the integrity of lipid rafts.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that hydrogen peroxide (H 2 O 2 ) and hypoxia (CoCl 2 ) induce apoptosis in cultured primary astrocytes [32][33][34]. Whether leptin has anti-apoptotic and necrotic effect on oxidative stress-induced apoptosis was evaluated using Annexin V-FITC/PI double staining monitored by flow cytometry.…”
Section: Leptin Has a Protective Effect Against Glutamate-induced Apomentioning
confidence: 99%